A new mayfly species of Choroterpes (Euthraulus) (Ephemeroptera: Leptophlebiidae) from South India - Rekha, Kalimuthu; Anbalagan, Sankarappan; Dinakaran, Sundaram; Balachandran, Chellapandian; Krishnan, Muthukalingan (Zootaxa, 2019)
A new mayfly species, Choroterpes (Euthraulus) kalladaensis sp. n. is described based on nymphs and subimagoes from South India. The nymph of Choroterpes (Euthraulus) kalladaensis sp. n. is characterized by a labrum with antero-median emargination well broad and ‘V’ shaped, femora with two black spots on median and basal region, claw with 2 sections of 13 denticles with 3 smaller serrations, posteriolateral spines present on segment 2–9, paraprocts smooth with pores and their inner margin with small triangular spines and outer margin with long setae and in the subimago the fore wing has four intercalary veins between costa and subcosta, penis lobes are short, membranous, separated apically and covered with minute setae. Taxonomic notes are given to distinguish this new species from closely related species.